2018
DOI: 10.1515/bps-2017-0023
|View full text |Cite
|
Sign up to set email alerts
|

Builders and Users of Ritual Centres, Yampil Barrow Complex: Studies of Diet Based on Stable Carbon and Nitrogen Isotope Composition

Abstract: The paper presents δ13C and δ15N isotope content measurements in human bones from 16 graves, being part of the Yampil Barrow Complex. From the results, conclusions may be drawn about the diet of barrow builders and users. It was based on vegetable foodstuffs and characterised by a varied share of terrestrial animal meat, depending on the period. High δ13C values suggest a share of C4-type plants in the diet, possibly millet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Early and Middle Bronze Age archaeobotanical assemblages from the wider region include rare finds of millet 88 , but these have not been dated. In contrast, the assemblages from the second half of the 2nd millennium bc, particularly the tail-end of the Late, and the Final Bronze Age (last quarter of the 2nd millennium bc 85 ), frequently contain remains of broomcorn millet 32,39,88,89 [74,75]. Sometimes these are concentrated grains, such as in one of the ceramic vessels hoarded in a pit at the Tumulus culture site of Lozorno, north of Bratislava in Slovakia 3 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early and Middle Bronze Age archaeobotanical assemblages from the wider region include rare finds of millet 88 , but these have not been dated. In contrast, the assemblages from the second half of the 2nd millennium bc, particularly the tail-end of the Late, and the Final Bronze Age (last quarter of the 2nd millennium bc 85 ), frequently contain remains of broomcorn millet 32,39,88,89 [74,75]. Sometimes these are concentrated grains, such as in one of the ceramic vessels hoarded in a pit at the Tumulus culture site of Lozorno, north of Bratislava in Slovakia 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Elevated δ 13 C values in human and animal bone collagen were explained by the seasonal consumption of C 4 plants naturally growing in the area, 70 73 . In the Yampil region on the Middle Dniester river (in the steppe zone), several individuals from the Early–Middle Bronze Age graves (late 3rd-first quarter of the 2nd millennium bc ) had collagen δ 13 C values of c. − 19.5‰ and were interpreted as possible millet consumers 74 . However, δ 13 C values more negative than − 18‰ do not indicate inclusion of C 4 plants in the diet 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Isotopic analyses. All carbon (δ 13 C coll ) and nitrogen (δ 15 N coll ) stable isotope analyses were performed at the Isotope Dating and Environment Research Laboratory at the Institute of Geological Sciences of the Polish Academy of Sciences in Warsaw 43 . Collagen was earlier extracted for AMS 14 C dating in the Poznań Radiocarbon Laboratory.…”
Section: Methodsmentioning
confidence: 99%
“…These higher values are then reflected in the measured δ 15 N values of all organisms who consume them, including humans with aquatic-rich diets. Comparative studies of individuals from different parts of Europe (Goslar et al 2017) have shown that the δ 15 N values of human bone collagen of individuals relying solely on terrestrial food sources were also subject to variation. In Giecz, ca.…”
Section: Methodsmentioning
confidence: 99%